Fires in nature: a review of the challenges for wild animals - GUTIÉRREZ, JARA; de Miguel, Javier (European Journal of Ecology, 2021)
Animals living in the wild are exposed to numerous challenges, such as fires, that can lead to suffering. The impacts of fire have been studied in different branches of ecology, but studies of its effects on the welfare of individual animals remain scarce. The current review aims to synthesize a sample of relevant aspects regarding fire’s negative effects on wild animals. We mainly focus on the immediate impacts of fire on individuals. How animals respond to fire depends on many factors including their life history, evolutionary adaptations to fire, and individual stress coping styles, in addition to the characteristics of the fire. The fundamentals of carrying out future work for animal rescue and prevention of animal harms in fires were also explored. Fires may increase the risk of injury, disease, stress, and mortality for animals living in the wild, resulting in physiological and psychological harm, experiences of suffering, discomfort and pain, and long-term detrimental consequences. Wild animals can benefit from effective rescue, rehabilitation, and release during fires, and post-release monitoring must accurately evaluate their outcome success. The resulting information can be used to educate veterinarians, rehabilitators, and the public in the prevention of the suffering and deaths of as many animals as possible in future fire events, which ultimately benefits animal welfare. This review provides a better understanding of how fire compromises animal welfare, providing an example of how to use the knowledge gathered in animal ecology to examine the welfare of wild animals. It can help raise concern for the situation of wild animals as individuals, and to develop the field of welfare biology, by identifying promising future lines of research.